2017
DOI: 10.1021/acs.analchem.7b02406
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of an Open Microfluidic Device for Immunoblotting

Abstract: Given the wide adoption of polydimethylsiloxane (PDMS) for the rapid fabrication of microfluidic networks and the utility of polyacrylamide gel electrophoresis (PAGE), we develop a technique for fabrication of PAGE molecular sieving gels in PDMS microchannel networks. In developing the fabrication protocol, we trade-off constraints on materials properties of these two polymer materials: PDMS is permeable to O2 and the presence of O2 inhibits the polymerization of polyacrylamide. We present a fabrication method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 42 publications
(101 reference statements)
1
22
0
Order By: Relevance
“…Different stacking efficiencies have been reported in previous microchip-based protein electrophoresis systems, depending on microchip design and geometry, gel matrices, buffers, and the electrophoretic conditions employed. Typically, sample injection dispersion was reduced by 50% to more than 90% in these systems [13,14,16,28,33,49,50], essentially similar or slightly better than our open microfluidic approach. Taken together, the implementation of a stacking boundary both increased the local protein concentration and reduced the sample injection dispersion, which may be favorable for the sensitivity of the immunoassay and the electrophoretic resolution, respectively.…”
Section: Sample Injection and Stackingmentioning
confidence: 71%
See 2 more Smart Citations
“…Different stacking efficiencies have been reported in previous microchip-based protein electrophoresis systems, depending on microchip design and geometry, gel matrices, buffers, and the electrophoretic conditions employed. Typically, sample injection dispersion was reduced by 50% to more than 90% in these systems [13,14,16,28,33,49,50], essentially similar or slightly better than our open microfluidic approach. Taken together, the implementation of a stacking boundary both increased the local protein concentration and reduced the sample injection dispersion, which may be favorable for the sensitivity of the immunoassay and the electrophoretic resolution, respectively.…”
Section: Sample Injection and Stackingmentioning
confidence: 71%
“…We speculate that this was caused by the detrimental effect of oxygen on the polymerization process and the effective compartmentalization of the precursor solution within the pores of the CA membrane. Including benzophenone or glycerol into the precursor solution, which were reported to act as oxygen scavengers during acrylamide polymerization [16,40], did not improve the reproducibility of the polymerization process (data not shown). Linear polyacrylamide derivatives were also tested, but protein migration was rather poor in these matrices, owing to severe evaporation effects during electrophoresis (including premature current breakdown) as a consequence of using linear polymers that do not form hydrogels.…”
Section: Paper-based Open Microfluidic Approachmentioning
confidence: 96%
See 1 more Smart Citation
“…After 30 s of SDS‐PAGE, the FITC‐BSA was quickly immobilized onto the photoclick gel under various ultraviolet light conditions (ranging from 20 to 100 s). The protein immobilization efficiency, [ 13 ] η, was defined as the ratio of FITC's fluorescence intensity before and after photoactive gel rinsing. Imaging data of the negative control results from UV irradiation time of 0 s in Figure 2c showed that the protein photoimmobilization under no UV condition is negligible, which indicated that the MMP gel remained inert without UV exposure under normal electrophoretic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…We implemented numerous innovations that enable a chemistry required to achieve single-cell ribosome profiling by coupling ITP with an optimized on-chip size selection. Specifically, we leveraged pretreatment of the channel with benzophenone to enable light-induced polymerization of polyacrylamide inside PDMS chips 14 . To aid visualization, we included DNA oligonucleotide markers containing a 5' fluorophore and 3' dideoxycytosine modification to prevent marker amplification in downstream library preparation (Extended Data Fig.…”
Section: Ribosome Profiling Via Isotachophoresis (Ribo-itp): An On-chip Methods For High Yield Extraction and Efficient Library Preparatimentioning
confidence: 99%